A Stakeholder analysis of the Soviet second economy - CHOI, Jae-hyoung (KDI School, 2015)
This research aims to demonstrate, through a stakeholder analysis, that the institutionalization of the second economy in the Soviet Union was a natural byproduct of the interaction among three major stakeholders of Soviet society: the state, the bureaucracy, and the people. The three stakeholders responded to the incentive structure of the socialist economic system, interacting with each other in order to enhance their own interests. This research argues that their interaction was the internal necessity or dynamics that formed this informal market mechanism and elevated it to a characteristic feature of Soviet society
Thesis(Master) --KDI School:Master of Public Policy,2015